INTERNAL FACTORS AFFECTING GROWTH OF SAVINGS AND CREDIT COOPERATIVE SOCIETIES IN MACHAKOS COUNTY, KENYA - Muithya, Victor K.; Ombati, PhD, Dr. Robert (European Journal of Business and Strategic Management, 2019)
Purpose: The Kenyan SACCO business plays a key role in contributing to the country's savings, that has boosted social development and the economy. The aim of the study was to establish the internal factors affecting the growth of Savings and Credit Cooperative Societies in Machakos County. Methodology: Descriptive research design was applied in the study whereby census was used for the whole chosen population. The 33 active SACCOs found in Machakos County formed the target population; purposive sampling was applied to select one hundred thirty-two (132) respondents. Questionnaires having open and closed ended questions relating to the objectives were used to collect primary data. Both descriptive and inferential statistics were applied in the study to analyze data from the questionnaires. SPSS version 21 software was used to code and analyze data. Tables were used in data presentation. Results: The study established that management skills positively and significantly affected the growth of SACCOs in Machakos County. The study established that loan portfolio management negatively and weakly affected the growth of SACCOs in Machakos County. The study indicates a weak positive relationship between human resources capacity and growth of SACCOs in Machakos County. The study established that the SACCOs in Machakos County have to some extent invested in IT, which has positively and significantly led to growth of the SACCOs. The study concluded that managerial skills, human resource capacity, adoption of Information Technology and loan portfolio management have influence on growth of SACCOs in Machakos County. Unique Contribution to Theory, Practice and Policy: Recommendations of the study are that the institutions should undertake an internal factor evaluation and practice of the administrative functions that impact the growth of SACCOs, policy guidelines should take its position in ensuring that SACCOs are operated in the best line of their expected performance obligations and there was still some room for further studies that would examine on the best factors to apply on the Kenyan SACCOs, that would enhance a more competitive SACCO business